Health Impacts of Volatile Organic Compounds in Pollution Control Zones of Industrial Areas: Historical, Current, and Future Perspectives - Soontornmon, Kaewalee; Bannawongsil, Thunyarut; Norkaew, Saowanee; Changsaluk, Jutarat; Tassaneetrithep, Boonrat (Thai Journal of Toxicology, 2025)
Thailand’s Map Ta Phut Industrial Estate emits high levels of benzene and 1,3-butadiene, yet evidence on chronic health harms remains fragmented. We systematically searched for studies published between January 2005 and December 2024 evaluating long-term health outcomes linked to occupational or residential volatile organic compounds (VOCs) exposure. Twenty-seven studies met the inclusion criteria; most involved petrochemical workers, and one-quarter focused on community residents living near industrial zones. Cross-sectional and registry-based designs predominated; heterogeneous exposure metrics precluded meta-analysis, so findings were narratively synthesized and bias appraised with Risk of Bias in Non-randomized Studies – of Exposures (ROBINS-E) tool. Consistent associations were found between benzene or 1,3-butadiene exposure and an increased risk of acute myeloid leukemia (AML), genotoxicity, and reduced white blood cells (WBC) counts. Over 75% of studies showed potential confounding or exposure misclassification; four were rated as high risk overall, highlighting methodological gaps. Nonetheless, post-2015 evidence supports a biologically plausible connection between sustained VOC exposure and carcinogenic, genotoxic, and haematotoxic outcomes. We recommend establishing a stricter regulatory tier for benzene and 1,3-butadiene in Rayong, which should include quarterly personal sampling, annual biomarker panels, integrated real-time and passive surveillance monitoring networks, and targeted maternal-child screening to protect vulnerable populations.